1982
DOI: 10.1073/pnas.79.17.5312
|View full text |Cite
|
Sign up to set email alerts
|

Serum contains a platelet-derived transforming growth factor.

Abstract: High concentrations of fetal bovine serum induced colony formation in soft agar by anchorage-dependent, nontransformed mouse AKR-2B and rat NRK cells. The colony-stimulating activity in fetal bovine serum was precipitated by 45% saturated ammonium sulfate and migrated in molecular sieve chromatography as a single peak of activity in the 10,000-15,000 molecular weight range. The colony-stimulating activity was heat and acid stable and was destroyed by trypsin and dithiothreitol, indicating the activity is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
1
2

Year Published

1983
1983
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(117 citation statements)
references
References 22 publications
2
112
1
2
Order By: Relevance
“…In addition, TGF like activity was found in both nonneoplastic and malignant effusion fluids. This finding is consistent with previous reports indicating TGF activity in nonneoplastic human and murine (Twardzik, et al, 1982) tissues and in human platelets (Assosian, 1983) and sera (Childs et al, 1982). It is therefore unlikely that simply assaying CM or sera for the presence of TGF-like activity can be used as a screen for malignant potential.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, TGF like activity was found in both nonneoplastic and malignant effusion fluids. This finding is consistent with previous reports indicating TGF activity in nonneoplastic human and murine (Twardzik, et al, 1982) tissues and in human platelets (Assosian, 1983) and sera (Childs et al, 1982). It is therefore unlikely that simply assaying CM or sera for the presence of TGF-like activity can be used as a screen for malignant potential.…”
Section: Discussionsupporting
confidence: 92%
“…Since TGF-,B mRNAs were expressed in our stromal cell cultures (Figure 5), active TGF-P could have been produced (among latent TGF-,B) by the stromal cells (Rowley, 1992b). On the other hand, the active fraction of inhibitor might consist of 'fibroblast-activated' latent TGF-P, for instance, present in the serum (Childs et al, 1982;Antonelli-Orlidge et al, 1989). Our data show that p-EIF has several properties in common with TGF-P, including reversibility of inhibition (Hebert and Birnbaum, 1989; Kooistra et al, 1995a) and sensitivity to trypsin and reducing agents.…”
Section: Discussionmentioning
confidence: 93%
“…Most cells, including stromal cells, secrete TGF-P as a latent complex which can be activated by treatment with heat, acid or proteases such as plasmin (Lawrence et al, 1985;Rowley, 1992b). Also, commercially available sera have been shown to contain latent TGF-P (Childs et al, 1982). The expression and activation appears to be influenced by steroid hormones (Kyprianou and Isaacs, 1989;Martikainen et al, 1990), as was shown also for urogenital sinus mesenchyme (Rowley, 1992b).…”
Section: Discussionmentioning
confidence: 99%
“…Harris, personal communication), stimulates differentiation and keratinization of normal, but not transformed human bronchial epithelial cells proliferating in a chemically defined medium, in a very similar manner to TPA (Willey et al, 1984), and hence might be expected to permit the same type of selective advantage to the initiated cells and their progeny if released in chemically initiated skin. The reports that the effect of TGF-# is synergistic with EGF to promote wound repair , and that it is found in platelets (Childs et al, 1982;Assoian et al, 1983) and clotted blood serum (Childs et al, 1982) but not plasma (Childs et al, 1982), suggest that the release of TGF-f may occur as part of the natural process of wound healing following damage to blood vessels. Blood vessel damage and the release of TGF-,B would accompany the promoting stimuli of skin wounding (Hennings & Boutwell, 1980;ClarkLewis & Murray, 1978;Marks et al, 1979) and to a lesser extent deep abrasion (Argyris, 1980a), but not the non-promoting stimuli of superficial abrasion (Marks et al, 1979) or skin massage (Clark-Lewis & Murray, 1978;Marks et al, 1979).…”
Section: Two-stage Epidermal Tumourigenesismentioning
confidence: 99%